Blueberry blunder - Flower, Amanda (Flower, Amanda. Amish candy shop mystery, 2023)
"Bailey King, star of TV's Bailey's Amish Sweets, is building her dream candy factory in Harvest, Ohio. But no sooner is the frame of the new building up than she finds the dead body of a surly contractor who has a long list of enemies--including people in the Amish community. To add to the drama, Bailey is being filmed by a crew for her upcoming show ... When Bailey's TV producer pitched a reality show about building the factory, Bailey was shocked that the network picked it up. She's not shocked that many of the Amish working on the jobsite refuse to be on camera. However, local community organizer Margot Rawlings is ecstatic--because the filming coincides with Harvest's First Annual Blueberry Bash. Margot believes the media attention will make Harvest the most popular destination in Holmes County. But now, the county may become known for all the wrong reasons ... Bailey will have to sift through a crowd of angry villagers and thousands of blueberries to solve the murder, save her new venture, and protect her Amish friends. At the same time, she and her longtime boyfriend, Aiden Brody, are making big decisions about their future together--a future that may be in jeopardy if Bailey is the next pick on a killer's list ..."-- Provided by publisher.